Question 375858: Hi, Totally Stuck here, not sure if the lecturer has skiped over this part,
Find dy=dx as a function of x and y when:
(a) y - x sin y - 3x^2 - 1 = 0
(b) x^2y^3 - x^2 + 3y - 3 = 0
(c) (1 - x^2) tan^-1 y = 3
Thanks Answer by Fombitz(13828) (Show Source):
You can put this solution on YOUR website! Use implicit differentiation, treat each terms as if it is differentiable (other than constants). Use the product rule, etc. to simplify. Gather up all of the dy and dx terms and then form the quotient, dy/dx.
I'll do one, you do the rest.